The expression (-2 - 6i)-(-2-4i) to a + bi form is 0 - 2i.
Complete question.
Simplify the expression to a + bi form:
(-2 - 6i)-(-2-4i)
Square root of any negative number are expressed as a complex number. For example i = √-1
Complex numbers are generally written in the format z = x+iy
Given the expression (-2 - 6i)-(-2-4i)), in expansion:
(-2 - 6i)-(-2-4i)
= -2 - 6i + 2+4i
Collect the like terms
= (-2 + 2) - 6i + 4i
= 0 - 2i
Therefore the expression (-2 - 6i)-(-2-4i) to a + bi form is 0 - 2i.
Learn more on complex number here: https://brainly.com/question/12375854